(untitled) (Revista LIDER, 2020)
The aim of this paper is to analyze the relationship between the introduction of neo-liberal reforms and the collective answers of urban popular sectors in Chile and Argentina. For one hand, it focuses on key aspects of the neo-liberal transformations, in particular those who operated on the State’s sphere and in the labor context. For the other hand, the social expressions elaborated by subordinate sectors in terms of social inequality outcomes generated by the new model are presented. This article introduces a comparative perspective between Argentina and Chile, which show a remarkable practice of the afore mentioned reforms.